Leksikon Padi dan Pertumbuhan Padi dalam Budaya Agraris Masyarakat Sunda di Bandung Barat: Lexicon of Paddy and Paddy Growth in the Agrarian Culture of Sundanese Community in West Bandung Regency - yusup irawan (Kantor Bahasa Provinsi Maluku, 2022)
This ethnolinguistic qualitative research aims to identify the lexicon of traditional paddy varieties and the lexicon of rice growth in the context of the Agraria culture of the Sundanese people. The Data collection involved seven local farmers in West Bandung Regency, West Java. The selection of research informants used a purposive sampling method. This research used a semantic field analysis approach with the perspective of linguistic relativity. The direct element division technique (BUL) and method distributional analyze these lexicons as the unit lingual. The study finds that local farmers classified paddy varieties into four groups of semantic fields, namely (1) pare ageung 'tall rice' (2) pare pendek 'short rice' (3) pare pusaka ''rice heirloom', (4) and pare ketan 'sticky rice '. The pattern of contiguity relations is more suitable to describe the relationship of meanings of the lexicon of traditional rice varieties in Sundanese culture. The close-meaning relationships have marked relationship patterns but have different features from one other. There were 17 lexicon names for traditional paddy varieties and one lexicon for naming hybrid rice varieties, with a local name called padi inul. Then, there were ten lexicons of paddies growth that described the process of rice growth. This study shows its relevance to the theory of linguistic relativity or the Sapir-Whorf Hypothesis. Keywords:Â Â culture, ethnolinguistics, lexicon, paddy, and Sundanese